Features of pneumonia on the background of chronic obstructive pulmonary disease: clinical case - Boakye-Yiadom Valentina (My University, 2019)
Актуальні питання сучасної медицини: Тези доповідей XVІ Міжнародної наукової конференції студентів, молодих вчених та фахівців 28-29 березня 2019 р. – Х.: ХНУ імені В. Н. Каразіна, 2019. – C. 320-321.
Scientific supervisors: assistant of department Skokova N.I., assoc. prof. Shevchuk M. I.
Keywords: pneumonia; chronic obstructive pulmonary disease